2020
DOI: 10.1038/s41598-020-60314-w
|View full text |Cite
|
Sign up to set email alerts
|

T-cell subset abnormalities predict progression along the Inflammatory Arthritis disease continuum: implications for management

Abstract: The presence of a disease continuum in inflammatory arthritis (IA) is a recognised concept, with distinct stages from at-risk stage (presence of anti citrullinated-peptide autoantibody) to diagnosis of rheumatoid arthritis (RA), including therapy-induced remission. Despite T-cell dysregulation being a key feature of RA, there are few reports of T-cell phenotyping along the IA-continuum. We investigated the disturbances of naïve, regulatory and inflammation related cell (IRC) CD4+ T-cell subsets in 705 individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 32 publications
5
30
0
Order By: Relevance
“…Self-activation of the memory T cells causes constant amplification of the disease. These lymphocytes release cytokines as IFN-γ and IL-2, which further activate monocytes and macrophages releasing subsequent IL-1, TNF-α and growth factors [93][94][95][96][97][98].…”
Section: Methotrexate-based Therapy Of Rheumatoid Arthritismentioning
confidence: 99%
“…Self-activation of the memory T cells causes constant amplification of the disease. These lymphocytes release cytokines as IFN-γ and IL-2, which further activate monocytes and macrophages releasing subsequent IL-1, TNF-α and growth factors [93][94][95][96][97][98].…”
Section: Methotrexate-based Therapy Of Rheumatoid Arthritismentioning
confidence: 99%
“…Relatively modest predictive importance of sociodemographic and clinical predictors in our study is in line with some earlier reports and reflects on clinical reality, wherein clinicians are unable to individualize methotrexate therapy in current practice. For example, in a study from the UK, baseline higher naive T cell frequency was found to be predictive of early RA remission at 6 months of first therapy with methotrexate, regardless of demographic, clinical, or other immunologic parameters, and it was proposed that naive CD4+ T cells can be predictive of progression of inflammatory arthritis (35,36). Taken together with our results, this suggests the role of assayable plasma biomarkers (e.g., genomics) relating to the immune system that prove to be vital in individualizing methotrexate therapy in treating early RA.…”
Section: Discussionmentioning
confidence: 99%
“…The origin of T cells in the synovium and how and where they have been activated is still largely unknown. Part of them may reflect activated resident T cells but probably the majority have been activated in peripheral lymphoid organs after which they then migrate to the synovium, as changes in the T cell compartment can be found in peripheral blood of early RA and RA-risk individuals (7,45,46). As previously highlighted, our work on LN-derived T cells suggest that there may be increased Tfh cells in RA patients (10) as well as a possibly exhausted population in RA-risk individuals (19,21) which are both characterized by increased PD1 expression.…”
Section: Insights From Synovium During Early Ra Developmentmentioning
confidence: 99%